How does age affect outcomes after left ventricular assist device implantation: results from the PCHF‐VAD registry. (2nd December 2022) - Radhoe, Sumant P.; Veenis, Jesse F.; Jakus, Nina; Timmermans, Philippe; Pouleur, Anne‐Catherine; Rubís, Pawel; Van Craenenbroeck, Emeline M.; Gaizauskas, Edvinas; Barge‐Caballero, Eduardo; Paolillo, Stefania; Grundmann, Sebastian; D'Amario, Domenico; et al.
Abstract: Aims: Use of left ventricular assist devices (LVADs) in older patients has increased, and assessing outcomes in older LVAD recipients is important. Therefore, this study aimed to investigate associations between age and outcomes after continuous‐flow LVAD (cf‐LVAD) implantation. Methods and results: Cf‐LVAD patients from the multicentre European PCHF‐VAD registry were included and categorized into those <50, 50–64, and ≥65 years old. The primary endpoint was all‐cause mortality. Among secondary outcomes were heart failure (HF) hospitalizations, right ventricular (RV) failure, haemocompatibility score, bleeding events, non‐fatal thromboembolic events, and device‐related infections. Of 562 patients, 184 (32.7%) were <50, 305 (54.3%) were aged 50–64, whereas 73 (13.0%) were ≥65 years old. Median follow‐up was 1.1 years. Patients in the oldest age group were significantly more often designated as destination therapy (DT) candidates (61%). A 10 year increase in age was associated with a significantly higher risk of mortality (hazard ratio [HR] 1.34, 95% confidence interval [CI] [1.15–1.57]), intracranial bleeding (HR 1.49, 95% CI [1.10–2.02]), and non‐intracranial bleeding (HR 1.30, 95% CI [1.09–1.56]), which was confirmed by a higher mean haemocompatibility score (1.37 vs. 0.77, oldest vs. youngest groups, respectively, P = 0.033). Older patients suffered from less device‐related infections requiring systemic antibiotics. No age‐related differences were observed in HF‐related hospitalizations, ventricular arrhythmias, pump thrombosis, non‐fatal thromboembolic events, or RV failure. Conclusions: In the PCHF‐VAD registry, higher age was associated with increased risk of mortality, and especially with increased risk of major bleeding, which is particularly relevant for the DT population. The risks of HF hospitalizations, pump thrombosis, ventricular arrhythmia, or RV failure were comparable. Strikingly, older patients had less device‐related infections.